Facies analysis of the Neoproterozoic to Late Cambrian Amadeus Basin, Central Australia - EL-Oshebi, Farag (Libyan Journal of Science &Technology, 2022)
The study aims to fill research gaps in sedimentology by presenting a sedimentological study of the Neoproterozoic to Late Cambrian section in the Eastern MacDonnell Ranges to the east of Alice Springs, northeastern area of the Amadeus Basin. This study used the facies analysis in order to improve the current understanding of lithofacies which assists in clarifying depositional environments interpretation in the northeast of the Amadeus Basin. This study recognised six lithofacies types (massive claystone, trough cross-stratification sandstone, hummocky cross-stratification sandstone, wave ripple lamination sandstone, massive siltstone, ripple cross-lamination sandstone) from the sedimentological log section. The Arumbera Sandstone and Shannon Formation were interpreted as deltaic settings. The Todd River Dolomite and Giles Creek Dolomite are possibly transitional marine to deltaic-peritidal setting. Sedimentological analysis in this study classified the Arumbera Sandstone and Todd River as arkoses and the Shannon Formation as dolostone.